Surabaya E-Peken Application In The Tam Approachment Method - Agus Sapto Purnomo (Riwayat: Educational Journal of History and Humanities, 2023)
The rapid development of communication technology has brought changes to various fields. One of the new things that have come about because of the growth of the internet is the ability to shop or buy things online. The city government of Surabaya made an app called E-PEKEN Surabaya for buying and selling locally online.Sellers and buyers of E-PEKEN Surabaya must continue to pay attention to the function of this application or called intention to use and the decision of sellers and buyers to continue using this application or called Actual System use PEKEN Surabaya application. intention to use and Actual System use in this application can be related to the theory of Technology Acceptance Model (TAM).